Hubungan Rendahnya Pemberian Asi Ekslusif Pada Ibu Bekerja Di TPMB Yuliani Kusrahmadani Tahun 2023 - Yuliani Kusrahmadani; Yulianti Yulianti (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
Exclusive breastfeeding is the provision of only breast milk without giving other food or drink to babies from birth to 6 months of age without anything additional except medication. The aim of the research is to determine the factors related to the low level of exclusive breastfeeding among working mothers at TPMB Yuliani Kusrahmadani 2023. It is hoped that it will be useful for mothers to increase their awareness in providing exclusive breastfeeding to babies appropriately, namely 0-6 months of age so that exclusive breastfeeding coverage can reach the target. which is supported by all groups. This type of quantitative research uses the Cross Sectional method. The population in this study was 50 respondents with a total sample of 50 breastfeeding mothers who had babies aged 6-12 months. The sampling technique is a total sampling technique. The research instrument used a questionnaire. Data analysis used univariate analysis and bivariate analysis with the chi-square test. The results of the research show that the variables related to exclusive breastfeeding in working mothers are knowledge p value = 0.007 OR value = 6.878, attitude p value = 0.009 OR value = 11.368, lactation facilities p value = 0.000 OR value = 11.667, family support p value = 0.000 OR value = 12.857, support from health workers p value = 0.000 OR value = 75,000. The conclusion from research conducted by researchers is that the factors that play an important role in determining exclusive breastfeeding for working mothers are knowledge, attitudes, lactation facilities, family support and support from health workers. Support from health workers is the highest risk factor for working mothers who do not breastfeed, namely 75,000.